2017
DOI: 10.1021/acs.biomac.7b01245
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight and Charge Density Effects of Guanidinylated Biodegradable Polycarbonates on Antimicrobial Activity and Selectivity

Abstract: Six guanidine functionalized aliphatic biodegradable polycarbonates with varying molecular weights and charge densities were synthesized via postsynthesis modification of alkyne containing polycarbonates using Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click chemistry. The concept of passive diluting group was to modify the cationic charge density of the polycarbonate without changing its hydrophilicity. Within the molecular weight range from 8000 to 30000 g mol, these guanidine polycarbonates exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…However, the antibacterial activity decreased for PLL 400 . Structure–activity relationship studies have shown that some antibacterial polycations, including guanidinylated polycarbonates (8–30 kDa) and guanylated polymethacrylates (3–20 kDa), are more effective at lower than higher MW. This difference has been attributed to the sieving effect of the bacterial membrane, reducing the ability of larger polymers to penetrate the membrane .…”
Section: Discussionmentioning
confidence: 99%
“…However, the antibacterial activity decreased for PLL 400 . Structure–activity relationship studies have shown that some antibacterial polycations, including guanidinylated polycarbonates (8–30 kDa) and guanylated polymethacrylates (3–20 kDa), are more effective at lower than higher MW. This difference has been attributed to the sieving effect of the bacterial membrane, reducing the ability of larger polymers to penetrate the membrane .…”
Section: Discussionmentioning
confidence: 99%
“…Aliphatic polycarbonates are well known for their degradability and biocompatibility. [ 34,35 ] Therefore, our “yne” component design is based on this polymer backbone. In 2016, Griesser's group reported the hydrolytic biodegradable photopolymers for the 3D printing of biomedical materials based on thiol‐yne click chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1980s, the idea that positively charged material has unique physiological effects to reduce the colony formation of bacteria was first proposed, and has become a key concept in the design of antimicrobial materials in recent decades. It is worth noting that the proper density of positive charges is one of the key factors for successful antimicrobial activity [ 11 , 20 , 21 , 22 , 23 , 24 ]. Pseudomonas aeruginosa and Staphylococcus aureus are two of the most common microbes that commonly lead to infections on wounds, and are also used to examine the antimicrobial function of materials in many studies [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the 1980s, the idea that positively charged material has unique physiological effects to reduce the colony formation of bacteria was first proposed, and has become a key concept in the design of antimicrobial materials in recent decades. It is worth noting that the proper density of positive charges is one of the key factors for successful antimicrobial activity [11,[20][21][22][23][24]. Pseudomonas…”
Section: Determination Of Antimicrobial Functionmentioning
confidence: 99%